Assessment of in vitro cytotoxicity of imidazole ionic liquids and inclusion in targeted drug carriers containing violacein. Issue 49 (10th August 2020) - Rivero Berti, Ignacio; Rodenak-Kladniew, Boris; Onaindia, Celeste; Adam, Claudia G.; Islan, German A.; Durán, Nelson; Castro, Guillermo R.
Abstract : Violacein (Viol) is a pigment produced by several Gram-negative bacteria with many bioactivities, such as anticancer, virucide, and antiparasitic. Abstract : Violacein (Viol) is a pigment produced by several Gram-negative bacteria with many bioactivities, such as anticancer, virucide, and antiparasitic. However, violacein is insoluble under physiological conditions preventing its potential therapeutic uses. Surface-active ionic liquids (SAILs) based on the cation 1-alkylimidazolium ([C n Him] ) with n = 10 to 16 alkyl carbon side chain lengths and acetate, bromide, methanesulfonate (S) or trifluoroacetate (F) as counterions were synthesized and screened to dissolve Viol in micellar aqueous media and for toxicological studies on the human lung carcinoma A549 cell line. Screening allowed the selection of 1.5 × 10 −3 % (w/v) [C16 Him]-S because it combines low cytotoxicity with 71.5% cell viability and good interaction with 95.2% of the violacein kept in micellar solution for at least 48 h. [Viol-([C16 Him]-S)] complex was used to develop an efficient hybrid solid lipid nanoparticle (SLN) carrier based on myristyl myristate and poloxamer 188 and tailored with folate to target cancer cells. Cellular SLN uptake was evaluated with fluorescent DiOC18 on A549, HCT-116, and HeLa cell lines expressing or not the folate receptor. The results showed fivefold incorporation of Viol nanoparticles in HCT-116 and HeLa cell cultures, displaying a high level of folate receptor. Biophysical characterization of the hybrid solid lipid carrier containing Viol was performed by dynamic light scattering, Fourier transform infrared, X-ray diffraction and X-ray photoelectron spectroscopies, and by transmission electron and cryo-transmission microscopies.